Temporal Expression of Angiogenesis-Related Genes in Developing Neonatal Rodent Retina: A Novel in Vivo Model to Study Cerebral Vascular Development - (:unkn) unknown (OXFORD UNIV PRESS INC, 2010)
BACKGROUND: Experimental models to study cerebrovascular malformations are limited therefore we used the neonatal rodent retina as a model to study cerebral angiogenesis. OBJECTIVE: We performed a gene expression analysis to define temporal changes in the expression of 96 angiogenesis-related genes during retinal vascularization. METHODS: A total of 72 retinas from 36 newborn C57BL/6 mice were used. Sets of neonatal mouse retinas were surgically isolated by 2-day intervals starting from postnatal day 0 to day 20 and at the 32nd day (representing adult retinas). For each of these 12 time points in the postnatal developmental period of mouse retinas, separate sets of 6 retinas from 3 mice were pooled, and their RNA was hybridized to an angiogenesis-specific gene array. Temporal expression patterns of each of the 96 angiogenesis-related genes were analyzed. For confirmation, vascular endothelial growth factor protein expression was also studied by immunohistochemistry. RESULTS: Twenty-two of the 96 genes analyzed displayed a significantly different temporal expression profile, and the rest exhibited a static expression, as compared to the human glyceraldehyde-3-phosphate dehydrogenase gene. Among these genes, the temporal pattern of expression was variable, but peaks were seen mostly on days 8, 10, 12, and 16. This timing corresponds well to morphologic changes that occur in the retina during different stages of angiogenesis. CONCLUSION: The neonatal rodent retina, which has a cellular architecture similar to that of the brain, has active and quantifiable angiogenic activity during the neonatal period and can be used as a simple and convenient model to study cerebral angiogenesis.
Keywords: Angiogenesis; Arteriovenous malformations; Cerebrovascular development; Gene expression array; Neonatal retina; HEREDITARY HEMORRHAGIC TELANGIECTASIA; ENDOTHELIAL GROWTH-FACTOR; DEVELOPING MOUSE RETINA; RAT CORNEA MODEL; ARTERIOVENOUS-MALFORMATIONS; MURINE MODEL; VASCULOGENESIS; TIME; MICE